Jehovah's Witnesses and transfusion: where do we stand in Europe?. (20th January 2020) - Loix, Sébastien; Henin, Pierre; Descamps, Olivier; Reusens, Isabelle
Abstract: Transfusion refusal expressed by Jehovah's Witnesses has always been questioning for medical community. However, abundant literature exists treating about how to manage difficult medical bleeding situations in Jehovah's witnesses, there is a few information available on the legal and ethical aspects of transfusion refusal. Since 1994, Europe has putted a spotlight on patient's right. The question of patient's autonomy and consent have taken a predominant place in care. In order to summarize the actual situation in Europe, this work intends to draw a global view on legal, ethical and medical aspects of transfusion refusal expressed by Jehovah witnesses.